Erratum: Stres Akademik dan Strategi Koping Siswa SMA dalam Fase Prapeminatan: Studi Metodologi Campuran (Buletin Riset Psikologi dan Kesehatan Mental, 2025)
Erratum: Hidayat, T., Efendi, A., & Musadad, A. A. (2025). Academic Stress and Coping Strategies Among High School Students in the Pre-specialization Phase: A Mixed-Methodology Study. Buletin Riset Psikologi Dan Kesehatan Mental (BRPKM), 5(2), 150–165. https://doi.org/10.20473/brpkm.v5i2.77300 In Articles titled  "Academic Stress and Coping Strategies Among High School Students in the Pre-specialization Phase: A Mixed-Methodology Study”, published 12 December 2025, Volume 5(2), There is a correction to the third sentence in the Abstrak that should be written as follows: “Hasil analisis data kuantitatif menunjukkan bahwa 23,1% siswa mengalami stres tingkat tinggi.“ as well as improvements to terminology "Kementerian Keuangan" in Deklarasi Potensi Terjadinya Konflik Kepentingan. The online version of corrected manuscript has been published.